2023
DOI: 10.1177/1358863x231159945
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients discharged with extended venous thromboembolism prophylaxis after hospitalization with COVID-19

Abstract: Background: Venous thromboembolism (VTE) is a known complication of coronavirus disease (COVID-19) in patients requiring hospitalization and intensive care. We examined the association between extended pharmacological VTE prophylaxis and outcomes among patients hospitalized with COVID-19. Methods: This was a retrospective cohort study of patients with an index positive SARS-CoV-2 polymerase chain reaction (PCR) test at the time of, or during hospitalization. Patients who were prescribed extended pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In the absence of contraindication, panellists recommended to initiate DOACs or switch to DOACs in patients diagnosed with AF during hospitalisation or in patients previously anticoagulated with VKAs, respectively. In a study with 1,936 hospitalised patients, VTE prophylaxis was associated with enhanced survival rates at 30 and 90 days and reduced likelihood readmission 30 days after discharge ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of contraindication, panellists recommended to initiate DOACs or switch to DOACs in patients diagnosed with AF during hospitalisation or in patients previously anticoagulated with VKAs, respectively. In a study with 1,936 hospitalised patients, VTE prophylaxis was associated with enhanced survival rates at 30 and 90 days and reduced likelihood readmission 30 days after discharge ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a large observational study of COVID-19 patients who never experienced thrombosis, no additional risk for VTE after hospitalization with acute SARS-CoV-2 infection was noted after hospital discharge 16 . Contrasting this, the MICHELLE study suggested a beneficial effect of an oral Factor Xa inhibitor on discharged patients by protecting against DVT if the patient was were previously hospitalized, even without an initial thrombotic event 17 .…”
Section: Introductionmentioning
confidence: 96%